Psychological needs and motivation of remote workers: sociological viewpoint - V. Yu. Pronin; V. V. Krivopuskov (Цифровая социология, 2023)
The article presents the findings of a sociological study, which uses Self-Determination Theory to describe and explain the motivation of remote workers. Representing a fundamentally different form of labor organization, remote work forms new conditions in which many management problems are solved, including motivation. An online survey conducted among Russian remote workers (N = 402) measured the satisfaction of three basic psychological needs (for autonomy, competence and relatedness) and six types of motivation, forming a continuum from amotivation to intrinsic motivation. According to the results, satisfaction of psychological needs creates conditions for the development of intrinsic motivation of remote workers, thus supporting Self-Determination Theory. The study also reveals that identified regulation and intrinsic motivation are more pronounced than other types of motivation. This may explain why in many studies remote workers are very positive regarding their remote work experience, in comparison with traditional forms of labor organization. The study thus confirms the applicability and value of Self-Determination Theory for explaining the features of remote work and designing optimal work organization models based on it.